Evolutionary robotics, organic computing and adaptive ambience epistemological and ethical implications of technomorphic descriptions of technologies - Decker, Michael 1965-; Knifka, Julia; Gutmann, Mathias 1966- (Lit, 2015)
Zusammenfassung: Literaturangaben
Keywords: Adaptives System; Agent -- Künstliche Intelligenz; Organic Computing; Ethik; Autonomes System; Embodiment; Erkenntnistheorie; Evolutionärer Algorithmus; Autonomer Roboter; Faktor Mensch; Konferenzschrift -- 2011 -- Karlsruhe